Design and Implementation of a Solar-Powered Load-Controlled Tower Crane Robot - Aliyu Badawi, Abubakar; Nasir Said, Ibrahim; Ayo Adewale, Abdulkadir (International Journal of Computer Sciences and Engineering, 2022)
In construction and heavy equipment sites, tower cranes are extensively used to hoist and move materials over a high-rise height. At present, there are some imperfections in the tower crane protection device. For the purpose of monitoring the time running state and eliminating the overloaded security issues of the tower crane, this paper proposes a way to implement a tower crane robot that consists of a load monitoring system using a load sensor, the objective of the system was to read weight carried by the tower crane in traditional analog to digital conversion, and also to attain high accuracy in measuring and calibrating the weight of the object. The components used for this research are a tower crane robot, an HX711 load cell amplifier, an Arduino-Uno microcontroller, an OLED display, a NEMA17 Stepper motor, and a DC motor. The load cell used in this research weighs 40kg. It sends an analog output signal to the HX711 module of the weight of the object, which converts it to digital, amplifies it, and sends it to the Arduino-Uno microcontroller and finally, the digital signal is sent to the OLED display. The robotic crane is made of the ‘MAST’, the main supporting tower of the crane. The ‘JIB’ is the operating arm of the crane, the ‘COUNTER JIB’ will be two-thirds the length of the jib used to carry the counter load, and the counter load will be movable along the axis of the counter jib in other to facilitate the process of counter-balancing.